Calibration of laser scanning intensity data using brightness targets - Vain, Ants; Kaasalainen, Sanna; Hyyppä, Juha; Ahokas, Eero (Geodesy and Cartography, 2012)
The paper examines a radiometric calibration method used at the Finnish Geodetic Institute (FGI). The brightness calibration targets and calibration scheme of airborne laser scanner intensity data is observed. For calibrating laser scanner intensity data, FGI has developed a system that contains portable brightness targets (tarps) with nominal reflectance from 5% to 70%. Also commercially available gravels and sands were tested for the use of calibration. A laboratory system was set up to measure intensity values under controlled conditions. The paper introduces a concept of calibrating ALS intensity data developed at FGI. Lazerinio skenavimo intensyvumo duomenų kalibravimas taikant šviesos taikinius Santrauka. Aprašomas Suomijos geodezijos institute taikomas radijometrinis kalibravimo metodas. Analizuojama stebėtų kalibravimo taikinių šviesumas ir lazerinio skenavimo intensyvumo duomenys. Lazerinio skenavimo intensyvumui kalibruoti institute sukurta sistema, kurią sudaro kilnojami šviesos taikiniai su nominaliniu atspindžiu nuo 5 % iki 70 %. Kalibravimo tikslams taip pat išbandyti taikiniai iš įprastinių žvyrų ir smėlių. Intensyvumo reikšmėms išmatuoti kontroliuojamose sąlygose buvo įkurta speciali laboratorija. First published online: 03 Aug 2012